Profil Internal Migrant Worker dan Lama Mencari Kerja di Banten - Anisa Rima Rahmawati; Rina Sri Kalsum Siregar (Universitas Muhammadiyah Tangerang, 2020)
Banten is the province with the highest unemployment rate. Its unemployment rate for some periods is higher than the national unemployment rate. Many jobs attract migrants to enter the Banten region. The large number of incoming migrants who are looking for work is not all absorbed by the labor market, thus increasing the number of unemployed people in Banten. This study aims to look at the description of internal migrant workers and local workers and determine the factors that determine the duration of job search in Banten. The data used is the 2017 Sakernas data. The unit of analysis is workers aged 15 years and over who worked 1 (one) years ago. The analytical method used is descriptive analysis and inferential analysis with survival analysis methods using the Cox Regression Model. The results showed that age, sex, marital status, education status, wage level, work experience, training, and employment status had a significant effect on the length of time someone was looking for work to be released from unemployment.